A Case Report of Juvenile Intraoral Pleomorphic Adenoma - Gupta Radhika; Chandavarkar Vidyadevi; Sinha Abhishek; Mishra Mithilesh (Indian Journal of Forensic Medicine & Toxicology, 2021)
Pleomorphic adenoma (PA) is the most common tumour of the salivary glands. About 90% of these tumours occur in the parotid gland and ten % in the minor salivary glands. The most common sites of Pleomorphic adenoma of the minor salivary glands are the palate, followed by lips and cheeks. Throat, floor of the mouth, tongue, tonsil, pharynx, retro molar area and nasal cavity are rarely involved. Pleomorphic adenoma typically present as a slow growing, unilateral and painless mass of salivary glands, with a predilection for recurrence and risk of malignant transformation (about 1.5% up to five years and increases to 9.5% after more than 15 years). This case report describes a case of Pleomorphic adenoma of buccal mucosa in a 13-year-old male patient.